2019
DOI: 10.1186/s13256-019-2140-6
|View full text |Cite
|
Sign up to set email alerts
|

Persistent response to vemurafenib in metastatic ameloblastoma with BRAF mutation: a case report

Abstract: Background Ameloblastomas are uncommon locally aggressive tumors of odontogenic epithelium that rarely metastasize. Currently, there is no standard of care for the metastatic forms. Several studies have shown that ameloblastomas frequently have a BRAF mutation. Case presentation We report a case of a 33-year-old Caucasian woman with ameloblastoma diagnosed 30 years ago who developed lung metastasis 19 years ago. Systemic oral treatment with vemurafenib, a BRAF inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…Besides, three cases with BRAF V600E mutation showed a successful response to BRAF inhibitors ( 18 - 20 ). It seems that BRAF inhibitors can have clinical benefits and responses in recurrent and metastatic ameloblastomas and use as neoadjuvant and/or targeted adjuvant therapy to improve the treatment outcome, especially in locally advanced ameloblastomas ( 21 , 22 ). Although new molecular medicine demonstrates personalized targeted therapy for ameloblastoma, it seems that based on lack of large scale clinical trials, evaluation of the wide clinical application of BRAF inhibitors has a long way.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, three cases with BRAF V600E mutation showed a successful response to BRAF inhibitors ( 18 - 20 ). It seems that BRAF inhibitors can have clinical benefits and responses in recurrent and metastatic ameloblastomas and use as neoadjuvant and/or targeted adjuvant therapy to improve the treatment outcome, especially in locally advanced ameloblastomas ( 21 , 22 ). Although new molecular medicine demonstrates personalized targeted therapy for ameloblastoma, it seems that based on lack of large scale clinical trials, evaluation of the wide clinical application of BRAF inhibitors has a long way.…”
Section: Discussionmentioning
confidence: 99%
“…Our case is the first reported attempt to treat a primary lesion with MAPK pathway inhibition, all other reports have involved recurrent or metastatic disease. [14][15][16][17][18][19] This is also the first reported case of treating ameloblastoma with MEKinhibition monotherapy. Our hope was that given the young age of this patient, she could be spared major reconstructive surgery.…”
Section: Discussionmentioning
confidence: 71%
“…13 In vitro studies have demonstrated the sensitivity of ameloblastoma cell lines to the BRAF inhibitor vemurafenib, and 2 case reports have shown good clinical response to the agent. 3,4,14,15 Similarly, there have been reported cases of ameloblastoma responding to the BRAF inhibitor dabrafenib, as well as to dual BRAF/MEK inhibition with dabrafenib/trametinib. [16][17][18][19] Here we present the case of a primary ameloblastoma in a pediatric patient that was treated with neoadjuvant single-agent MEK inhibitor therapy prior to any invasive surgical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…BRAF mutations have been detected in a high proportion of ameloblastoma cases, typically exceeding 50% according to a recent systematic review [18]. Early case reports present an impressive short-term response of both primary and metastatic sites to BRAF inhibitors, succeeding considerable symptomatic relief and tumour size reduction [19]. However, the follow-up period in these reports is typically very short.…”
Section: Discussionmentioning
confidence: 99%